Pacaa Nova : Clash of Cultures on the Brazilian Frontier - Von Graeve, Bernard, 1941- (Book collections on Project MUSE., 1989)
The Pacaa Nova were originally a tribe of hunters, gatherers and simple horticulturalists in the upper Amazon. As the frontier of Brazilian 'civilization' has expanded, their extraordinary culture has been trampled on and transformed. Of particular importance in this case has been the intrusion of the rubber industry into the Amazon headwaters; important as well have been the influences of the Catholic Church and the government. It is a tragic story, but an entirely fascinating one, and von Graeve presents it in enormously readable fashion, with first-hand descriptions that bring the people to life for the student.